Implementation of international experience of legal regulation of public employees' labor rights - I. O. Sievidova; L. V. Mohilevskyi; V. V. Sychova (Law and Safety)
The paper covers analysis of the international experience of legal regulation of labor rights of public service employees. The influence of the standards of the International Labor Organization on the labor law of Ukraine has been studied. The scope of labor legislation on the regulation of state employees’ labor has been established. It has been concluded that ratification and compliance with international standards of labor organization is one of the promising areas of the country’s development and improving its international image as a democratic and socially oriented state.